Ференц Ліст на Вінниччині: міфи та факти - Кушка, Н. (Студії мистецтвознавчі, 2007)
This article is devoted to the great composer of the 19th century Ferentz Liszt. It contains little known facts of composer's stay in Podolya Region (Ukraine) in 1847. There is the description of Ferentz Liszt's romance with Karolina Wittgenshtein, his life in her own estate in Voronintzy village (now Khmelnik's District of Vinnitsa Region). Also you can find some corrections and specifies those moments, that were misinterpråted in other sources of literature.